Pengaruh Penggunaan Jenis Busi Terhadap Emisi Gas Buang Motor Bakar 100 Cc Menggunanakan Bahan Bakar Alternatif Dari Limbah Plastik - Aprizal, Aprizal; Slamat, Slamat; Rizal, Yose; Fathoni, Ahmad (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to determine the exhaust emissions of 100 CC motorcycle engines with variations of Nickel Alloy and Iridium spark plugs. As well as the use of BBA and BBK fuels at idle engine speed. This research method is experimental by testing carbon monoxide (CO), Hydrocarbons (HC), Carbon Dioxide (CO2), Oxygen (O2) using the Hesbon Analyzer HG-520 tool. The results of testing the use of Nickel Alloy spark plugs with BBA obtained a result of (CO) 3.13%, testing (HC) obtained 1580%, and (O2) obtained a value of 20.76%, while testing using Iridium spark plugs with BBA obtained a result of CO 1.01%, HC obtained 764 ppm, CO2 obtained 0% and O2 obtained 21.16%. The conclusion is that exhaust emissions in the Nickel Alloy and Iridium spark plug variation testing using alternative fuels, get better results (CO) and (HC) on Iridium spark plugs while O2 is better on Nickel Alloy spark plugs. In the BBK test, the results of CO and HC are the same, while O2 is better on Iridium spark plugs.